2020
DOI: 10.29052/ijehsr.v8.i3.2020.145-152
|View full text |Cite
|
Sign up to set email alerts
|

Association of Grip Strength with obesity & cortisol; Possible indicators of biological ageing

Abstract: Background: Cortisol has a positive correlation with obesity, which indicates a relation between obesity and cortisol. Furthermore, there are increased chances of demolished muscle strength up to two times with elevated levels of cortisol. Thus, the aim of the study was to assess the impact of increased cortisol levels on the grip strength and to determine that the grip strength is a possible indicator for accelerated biological ageing. Methodology: This cross-sectional, purposive sampling study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The average value of hand grip strength in current study is 31.81 ± 14. 85 kg while, another Pakistani study's hand grip strength outcome was 30.75± 14.35 kg which is in congruence with the current findings (Mirza et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The average value of hand grip strength in current study is 31.81 ± 14. 85 kg while, another Pakistani study's hand grip strength outcome was 30.75± 14.35 kg which is in congruence with the current findings (Mirza et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…A study also concluded that value of the mean of the handgrip strength was significantly marked in boys than girls (Jawaria, 2018). A research study conducted in city of Karachi, Pakistan concluded that the muscle strength as well as hand grip strength was low in females as compared to males (Mirza et al, 2020). A study of Pakistani population in as well as Columbian are also in congruence and also showed that hand grip strength in females is lower than males, this also demonstrates that low females have low muscle strength as compared to males regardless of age specification (Jawaria, 2018, Ramírez-Vélez et al, 2015.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations